Disparities in Access to Cancer Diagnostics in ASEAN Member Countries - Alberto, Nicole Rose I. (Archīum Ateneo, 2023)
Diagnostics, including laboratory tests, medical and nuclear imaging, and molecular testing, are essential in the diagnosis and management of cancer to optimize clinical outcomes. With the continuous rise in cancer mortality and morbidity in the Association of Southeast Asian Nations (ASEAN), there exists a critical need to evaluate the accessibility of cancer diagnostics in the region so as to direct multifaceted interventions that will address regional inequities and inadequacies in cancer care. This paper identifies existing gaps in service delivery, health workforce, health information systems, leadership and governance, and financing and how these contribute to disparities in access to cancer diagnostics in ASEAN member countries. Intersectoral health policies that will strengthen coordinated laboratory services, upscale infrastructure development, encourage health workforce production, and enable proper appropriation of funding are necessary to effectively reduce the regional cancer burden.